Empowering Future Educators: Leveraging Openness by Design when Integrating Technology in Teacher Education Programs - Michael Paskevicius (Edutec, 2023)
Teacher educators who design and teach educational technology courses have an important role to play in developing thoughtful approaches to using educational technology in teaching and learning through the development of digital literacies that make use of accessible, meaningful, and pedagogically appropriate technology. Several researchers have argued that K-12 teachers are well suited to both adopt and develop aspects of open education by growing awareness of open educational resources and practices. This paper aims to articulate the potential, gaps, and opportunities for teacher educator programs to bring aspects of open education into teacher training. Based upon a small survey with students in a teacher education program in British Columbia Canada, gaps in knowledge among teacher candidates are identified and reflections from participants provides motivation to consider how open educational resources and practices might be further integrated into teacher education programs. Kahle’s (2008) design philosophy approach is recommended and discussed based on the results with a focus on using technology to prioritize openness that aligns well to prominent themes in teacher education programs.